Inflammatory biomarkers and therapeutic potential of milk exosome-mediated CCL7 siRNA in murine intestinal ischemia-reperfusion injury - Chen, WenDong; Xu, WenPing; Ma, Li; Bi, Chun; Yang, MeiXu; Yang, Wei (Frontiers in Immunology, 2025)
BackgroundIntestinal ischemia-reperfusion injury (IIRI) is a severe clinical condition associated with high morbidity and mortality. Despite advances in understanding the pathophysiology of IIRI, effective diagnostic and therapeutic strategies remain limited.MethodsUsing transcriptome sequencing in a mouse model of IIRI, we identified potential biomarkers that were significantly upregulated in the IIRI group compared to the sham group. Based on these findings, we developed and evaluated a therapeutic strategy using milk-derived exosomes loaded with siRNA targeting CCL7 (M-Exo/siCCL7).ResultsFocusing on Ccl7 as a hub gene, we explored the therapeutic efficacy of milk-derived exosomes loaded with siRNA targeting Ccl7 (M-Exo/siCCL7) in the IIRI model. M-Exo/siCCL7 treatment effectively attenuated intestinal inflammation and injury, as evidenced by reduced histological damage, decreased serum markers of intestinal barrier dysfunction, and attenuated systemic inflammation.ConclusionOur findings provide new insights into the molecular mechanisms underlying IIRI, identify potential diagnostic biomarkers, and highlight the promise of exosome-based siRNA delivery as a novel therapeutic approach for IIRI.